Auditory Processing Differences Correlate With Autistic Traits in Males - Aykan, Simge; Gürses, Emre; Tokgöz-Yılmaz, Suna; Kalaycıoğlu, Canan (Frontiers in Human Neuroscience, 2020)
Autism spectrum disorder (ASD) has high prevalence among males compared to females but mechanisms underlying the differences between sexes are poorly investigated. Moreover, autistic symptoms show a continuity in the general population and are referred to as autistic traits in people without an ASD diagnosis. One of the symptoms of ASD is sensory processing differences both in sensitivity and perception. To investigate sensory processing differences in autistic traits, we examined auditory and visual processing in a healthy population. We recruited 75 individuals (39 females and 36 males, mean age = 23.01 years, SD = 3.23 years) and assessed autistic traits using the Autism Spectrum Quotient, and sensory sensitivity using the Sensory Sensitivity Scales. Sensory processing in the visual domain was examined with the radial motion stimulus and the auditory domain was assessed with the 1,000 Hz pure tone stimulus with electroencephalography-evoked potentials. The results showed that the auditory sensitivity scores of the males (raud (34) = 0.396, paud = 0.017) and the visual sensitivity scores of females were correlated with autistic traits (rvis (37) = 0.420, pvis = 0.008). Moreover, the P2 latency for the auditory stimulus was prolonged in the participants with a higher level of autistic traits (rs (61) = 0.411, p = 0.008), and this correlation was only observed in males (rs (31) = 0.542, p = 0.001). We propose that auditory processing differences are related to autistic traits in neurotypicals, particularly in males. Our findings emphasize the importance of considering sex differences in autistic traits and ASD.